N-Arylation of Protected Azamacrocycles - Veiga, Alberte X.; Arenz, Sven; Erdélyi, Máté (Synthesis, 2013)
A rapid method for efficient palladium-catalyzed N-arylation of polynitrogenated macrocycles is presented. Its applicability for functionalization of protected azamacrocycles of various sizes with substituted aryl bromides of optional electronic properties is demonstrated. The compatibility of the protocol with common N-protecting schemes as well as the impact of electronic versus steric factors is discussed. Using a commercially available catalytic system and easily available alkoxide or phenoxide base, the method provides moderate to excellent yields of N-arylated azamacrocycles (45–96%).
Keywords: azamacrocycles; N-arylation; C–N coupling; heterocycles; homogeneous catalysis